DTU i isolates of Trypanosoma cruzi induce upregulation of Galectin-3 in murine myocarditis and fibrosis - Ferrer, Maria Florencia (2014)
Chagas heart disease is a major public concern since 30% of infected patients develop cardiac alterations. The relationship between Trypanosoma cruzi discrete typing units (DTUs) and the biological properties exhibited by the parasite population has yet to be elucidated. In this study, we analysed the expression of α-smooth muscle actin (α-SMA) and galectin-3 (Gal-3) associated with cardiac extracellular matrix (ECM) remodelling a murine chronic cardiomyopathy induced by Tc I genotypes. We found the induction of myocarditis was associated with the upregulation of Col I, α-SMA, Gal-3, IFN-γ and IL-13, as analysed by q-PCR. In myocardial areas of fibrosis, the intensity of myocarditis and significant ECM remodelling correlated with the presence of Col I-, Gal-3-and α-SMA-positive cells. These results are promising for the further efforts to evaluate the relevance of Gal-3 in Chagas heart disease, since this galectin was proposed as a prognosis marker in heart failure patients.